Cash Transfers in an Epidemic Context : The Interaction of Formal and Informal Support in Rural Malawi - Strobbe, Francesco; Miller, Candace (2012)
This paper investigates the short-run consumption expenditure dynamics and the interaction of public and private arrangements of ultra-poor and labor-constrained households in Malawi using an original dataset from the Mchinjii social cash transfer pilot project (one of the first experiments of social protection policies based on unconditional cash transfers in Sub-Saharan Africa). The authors exploit the unique source of exogenous variation provided by the randomized component of the program in order to isolate the effect of cash transfers on consumption expenditures as well as the net crowding out effect of cash transfers on private arrangements. They find a statistically significant reduction effect on the level of consumption expenditures for those households receiving cash transfers, thus leading to the rejection of the perfect risk sharing hypothesis. Moreover, by looking at the effects of cash transfers on private arrangements in a context characterized by imperfect enforceability of contracts and by a social fabric heavily compromised by high HIV/AIDS rates, the analysis confirms the presence of crowding out effects on private arrangements when looking at gifts and (to a lesser extent) remittances, while informal loans seem to be completely independent from the cash transfer's reception. From a policy perspective, the paper offers a contribution to the evaluation of the very recent wave of social protection policies based on (unconditional) cash transfers in Sub-Saharan Africa, suggesting that there might be an important role for public interventions aimed at helping households to pool risk more effectively.